1995
DOI: 10.1108/09564239510091358
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of halo effects in satisfaction measures of service attributes

Abstract: Many service firms measure satisfaction or quality on an attribute level. Halo effects between attributes have been shown to exist in many contexts mainly in social psychology and human resource management. In marketing, halo effects have been examined nearly exclusively in consumer decision making. Examines for the first time the existence of halo effects in consumer satisfaction. Employs a true experimental design. Expectations and performance of a single service attribute were manipulated and all other attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 39 publications
1
63
0
Order By: Relevance
“…A variety of studies have also shown that increases in system response delay lead to negative affective responses, such as anxiety (Guynes, 1988;Schleifer & Amick, 1989). Additional studies have shown that system delays can negatively impact other measures such as satisfaction with the system itself (Rushinek & Rushinek, 1986;Wirtz & Bateson, 1995).…”
Section: Computer-based Delay and Download Time Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…A variety of studies have also shown that increases in system response delay lead to negative affective responses, such as anxiety (Guynes, 1988;Schleifer & Amick, 1989). Additional studies have shown that system delays can negatively impact other measures such as satisfaction with the system itself (Rushinek & Rushinek, 1986;Wirtz & Bateson, 1995).…”
Section: Computer-based Delay and Download Time Researchmentioning
confidence: 96%
“…Attitudes such as attitude toward the delay and attitude toward the particular page may also have a significant impact on overall attitude toward the retailer. In fact, service response time studies have shown that attitude toward wait time is an important predictor of negative consequences (Chebat & Filiatrault, 1993;Wirtz & Bateson, 1995).…”
Section: Consumer Attitudesmentioning
confidence: 99%
“…Customer satisfaction not only maintains relationships with old customers, it is also cost-saving compared to the method of securing new customers. Moreover, through old customers' higher tendency to repeat purchase and through their positive word of mouth to win new customers, customer satisfaction has a significant effect on profit gaining power (Wirtz and Bateson, 1995). Basically, customer satisfaction is a direct factor to explain customer loyalty and is an important factor in determining customer retention and entrepreneurial profits (Shih, Chan, Chu, and Huang, 2008).…”
Section: Relationship Qualitymentioning
confidence: 99%
“…Therefore, where performance matches or exceeds customer expectations there will be positive disconfirmation and customer satisfaction. However, negative disconfirmation will occur where performance is below customer expectations and there is customer dissatisfaction (Wirtz and Bateson, 1995). The gap between customer evaluation or perceptions of performance and customer satisfaction provide a solid measure of service quality and determines the level of performance (Thijs and Staes, 2008: 15).…”
Section: Customer Satisfactionmentioning
confidence: 99%